Pembaharuan Sanksi Tindakan Kebiri Kimia Terhadap Pelaku Kekerasan Seksual Oleh Paedofil (Mimbar Keadilan, 2023)
The purpose of this research is to describe chemical castration sanctions that need to be renewed. This research uses a legal approach and a conceptual approach. Chemical castration raises pros and cons in its application as an action sanction, where the sanction has an educational nature, not as a form of retaliation. Chemical castration sanctions are applied to perpetrators of sexual violence against children. Even though it has been classified for anyone who can receive sanctions in the form of chemical castration, the rule does not mention what if the perpetrator is classified as a pedophile, where a pedophile is an adult who repeatedly performs sexual acts with prepubertal children. There needs to be scientific research related to how pedophiles can be stopped or cured because if seen from what is called a pedophile and the prohibitions mentioned in the child protection law are the same. The concept of renewing sanctions that must then exist is where the application of chemical castration is abolished and replaced with rehabilitation, but it is necessary to conduct research on whether these perpetrators are classified as pedophiles. carry out the punishment that is in effect today, because the possibility of the perpetrator committing the act repeatedly is quite high considering that chemical castration is not permanent like conventional castration is permanent. If possible, there will be new regulations in the form of revisions to laws and/or issuance of government regulations.